Pyrolysis and flammability behavior of long (Glass fiber)‐Reinforced polyamide 6 by aluminum alkylphosphinate‐based flame retardants in combination with organic montmorillonite. Issue 1 (28th September 2015) - He, Wentao; Zhu, Huan; Zhang, Pengcheng; Xiang, Yushu; Zhou, Ying; Qin, Shuhao; Yu, Jie
Abstract : The pyrolysis and flammability behavior of long (glass fiber)‐reinforced polyamide 6 containing aluminum alkylphosphinate‐based flame retardant in conjunction with montmorillonite or organic montmorillonite (OMMT) were investigated by using thermal gravimetry, limiting oxygen index, vertical burning test, and cone calorimeter measurements. The results revealed that the incorporation of OMMT in (aluminum alkylphosphinate)‐containing long (glass fiber)‐reinforced polyamide 6 did not significantly affect the thermal stability; however, they showed an obvious synergy on the char yield. The components from the flame retardant, especially phosphorus, acted in the gas phase and condensed phase simultaneously. Substitution of part of flame retardants with OMMT helped keep more phosphorus in the solid phase at the expense of gas‐phase activity, as demonstrated in scanning electron microscopy‐energy‐dispersive X‐ray characterization of the residue. This substitution constructed an impermeable barrier on the burning surface, which was responsible for the improvements in the vertical burning test classification and limiting oxygen index test. J. VINYL ADDIT. TECHNOL., 24:27–36, 2018. © 2015 Society of Plastics Engineers